2021
DOI: 10.3390/ijms22031074
|View full text |Cite
|
Sign up to set email alerts
|

The MHC Class II Transactivator CIITA: Not (Quite) the Odd-One-Out Anymore among NLR Proteins

Abstract: In this review, we discuss the major histocompatibility complex (MHC) class II transactivator (CIITA), which is the master regulator of MHC class II gene expression. CIITA is the founding member of the mammalian nucleotide-binding and leucine-rich-repeat (NLR) protein family but stood apart for a long time as the only transcriptional regulator. More recently, it was found that its closest homolog, NLRC5 (NLR protein caspase activation and recruitment domain (CARD)-containing 5), is a regulator of MHC-I gene ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 157 publications
(230 reference statements)
2
48
0
Order By: Relevance
“…Since the entire cluster of HLA II genes were down regulated by EBNA2, we suspected that these effects are mediated through the master transcriptional regulator of HLA-II CIITA [ 40 ]. Analysis of published ChIP-seq data revealed that EBNA2 and CIITA both bound to numerous sites across the HLA-class II region ( Fig 4A ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since the entire cluster of HLA II genes were down regulated by EBNA2, we suspected that these effects are mediated through the master transcriptional regulator of HLA-II CIITA [ 40 ]. Analysis of published ChIP-seq data revealed that EBNA2 and CIITA both bound to numerous sites across the HLA-class II region ( Fig 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…CIITA was identified as a transcriptional coactivator essential for expression of HLA-class II genes. Its expression correlates tightly with HLA-II gene transcription, and is mostly restricted to lymphoid cells [ 40 ]. CIITA is known to be regulated through multiple cell-type specific promoter and distal enhancers that make a network of contacts with each promoter [ 40 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The NLRA subfamily comprises of a sole member, namely: the Class II Major Histocompatibility Complex Transactivator (CIITA), which contains an N -terminal acidic transactivation domain, but also a CARD domain, a nuclear localization signal and four LRRs [ 16 ]. CIITA has been recognized as the “master regulator” of Major Histocompatibility Complex (MHC) class II molecule (MHC-II) expression since it controls the differential expression of MHC-II genes [ 17 ].…”
Section: The Nlra Subfamilymentioning
confidence: 99%
“…In mice and humans, CIITA expression is regulated by three and four distinct promoters, respectively, resulting in different isotypes [ 16 , 22 ]. Human keratinocytes mainly express type IV CIITA transcribed from promoter IV upon IFN-γ stimulation [ 22 ], which can be further induced by interleukin (IL)-18 [ 27 ], which subsequently leads to MHC-II expression [ 22 ].…”
Section: The Nlra Subfamilymentioning
confidence: 99%